COMPACTAÇÃO DO SOLO POR COLHEDEIRA DE FORRAGEM EM UMA CAPINEIRA DE CAPIM ELEFANTE - Ribeiro, Sérgio Ari; Marcos, Zilmar Ziller; Marcos, Zilmar Ziller; Lima, César Gonçalves de; Lima, César Gonçalves de; Luz, Pedro Henrique de Cerqueira; Luz, Pedro Henrique de Cerqueira (REVISTA DE AGRICULTURA, 2020)
COMPACTAÇÃO DO SOLO POR COLHEDEIRA DE FORRAGEM EM UMA CAPINEIRA DE CAPIM ELEFANTE